Effectiveness of electroacupuncture for thin endometrium in infertile women: study protocol for a single-blind, randomized controlled trial - Fangyuan Li; Hua Lu; Xinxin Wang; Qi Zhang; Qianchen Liu; Tong Wang (figshare, 2021)
Abstract Background Thin endometrium negatively impacts the reproductive function. Current treatments for thin endometrium do not always improve endometrial receptivity. Preliminary evidence suggests that electroacupuncture could have potential therapy for thin endometrium in infertile women. Thus, this randomized controlled trial was designed to test whether electroacupuncture can improve endometrial receptivity in infertile women with thin endometrium. Methods This study is a randomized, single-blinded, controlled, clinical trial. A total of 142 eligible patients will be recruited and randomly assigned to the electroacupuncture (EA) group or the sham electroacupuncture (SEA) group in a 1:1 ratio. Participants will receive 36 sessions over three menstrual cycles (12 weeks in total), with the same acupoint prescription. The primary outcome of this trial is endometrial thickness in the midluteal phase. The secondary outcomes include endometrial pattern, resistance index (RI) and pulsatility index (PI) of bilateral uterine artery and endometrium blood flow, serum estradiol (E2) and progesterone (P), and pregnancy rate. The pregnancy rate will be evaluated during a 6-month follow-up after completion of the trial. All other outcomes will be evaluated before treatment, during the treatment of 1st, 2nd, and 3rd menstrual cycle, and 6 months after treatment. Discussion If the outcome confirms the effectiveness of electroacupuncture for thin endometrium in infertile women, this treatment will be proposed for application in clinical practice. Trial registration Chinese Clinical Trials Registry ChiCTR2 000029983. Registered on 18 February 2020
Keywords: Medicine; Cell Biology; Physiology; Pharmacology; Biotechnology; Chemical Sciences not elsewhere classified; Immunology; Mathematical Sciences not elsewhere classified; Cancer; Science Policy; Mental Health; Infectious Diseases